Visualizing and modeling cloud for virtual environment - Mohd. Shahrizal Sunar 202579; Mohammad Azam Rana 305257; Sarudin Kari 191261; IASTED International conference on Applied Simulation and Modelling (2003 : Marbella, Spain) 479861 (Skudai : Universiti Teknologi Malaysia, 2003)
20